The effects of nitrofurantoin on rat urinary bladder contraction - Kacar, Emine; Ercan, Zubeyde; Tan, Fatih; Zorlu, Gökhan; Bulmuş, Özgür; Serhatlioglu, İhsan (My University, 2019)
Nitrofurantoin is a drug used in the antibacterial treatment of urinary tract infections (UTIs) for over 60 years. The aim of our study was to investigate the possible effects of nitrofurantoin, which is commonly used as a urinary tract antiseptic, on bladder contractions in male rats. Bladder tissues obtained from male Sprague-Dawley rats were used in the study (n=24). After decapitation, bladder tissues were suspended in an isolated organ bath of 5 ml containing a Krebs-Ringer bicarbonate solution by applying a tension of 1.5 grams. Nitrofurantoin was administered to three groups at doses of 50, 500 and 1000 ?M, respectively. The area, peak-to-peak (p-p) and frequency values of bladder contractions were analyzed before and after administration of nitrofurantoin. The data obtained from the analysis were evaluated using the Paired T-Test in the IBM SPSS Statistics Software. Nitrofurantoin was observed to have an inhibitory effect on bladder contractions at all doses. The decrease in the area and peak-to-peak values was statistically significant at all doses (P<0.05). It has been observed that nitrofurantoin inhibited bladder contractions. Based on these findings, it is thought that the fact that frequent urination, which is commonly seen in UTIs, is reduced after nitrofurantoin therapy may be due to the inhibitory effect of nitrofurantoin on bladder contractions.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp